2017
DOI: 10.3144/expresspolymlett.2017.91
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial polymeric nanocomposites synthesized by in-situ photoreduction of silver ions without additives inside biocompatible hydrogel matrices based on N-isopropylacrylamide and derivatives

Abstract: Abstract. Synthesis of antibacterial nanocomposite obtained by in-situ photoreduction of Ag+ ions impregnated inside a biocompatible hydrogel matrix is described. Hydrogel matrixes based on N-isopropylacrylamide (PNIPAM) and copolymers are synthesized by free radical polymerization in aqueous medium. The hydrogels are loaded with Ag + ions and then silver nanoparticles (Ag-NPs) are obtained in-situ by application of UV light without using additives. Ag-NPs formation inside hydrogels is confirmed by UV-visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…PNIPAM-co-2%AMPS was an exceptional case with a behavior similar to previously reported work [26]. Possibly, lower Pc value at pH 2 than pH 7 is related to the low swelling capacity of matrix at that pH or with the absence of anionic groups to interact with Ag + ions.…”
Section: Partition Coefficients Of Ag + Ionssupporting
confidence: 85%
See 2 more Smart Citations
“…PNIPAM-co-2%AMPS was an exceptional case with a behavior similar to previously reported work [26]. Possibly, lower Pc value at pH 2 than pH 7 is related to the low swelling capacity of matrix at that pH or with the absence of anionic groups to interact with Ag + ions.…”
Section: Partition Coefficients Of Ag + Ionssupporting
confidence: 85%
“…In this work, acidic hydrogels obtained by copolymerization of N-isopropylacrylamide (NIPAM) and methacrylic acid (MAA) monomers were proposed as matrixes generator of Ag-nanocomposites. Biocompatibility of matrixes based on NIPAM [27,28] and the antibacterial effect of Ag-nanocomposites based on these matrixes were previously demonstrated [26].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The UV-Vis spectra of both AgNO 3 solution and Borax added-AgNO 3 solution showed a peak corresponding to Ag + ions at 300 nm [42] (black arrow) (Figure 2 A). But, this peak was not observed in the spectrum of ADA-AgNO 3 solution.…”
Section: Uv-visible Spectroscopy Of Ada-agnpsmentioning
confidence: 99%
“…However, PVDF-Ag and PVDF-GO-Ag membranes can inhibit bacteria from attaching to the membrane surfaces by releasing Ag + ions. Very recently, Monerris et al [79] reported that hydrogel nanocomposites loaded with AgNPs show antibacterial activity by releasing Ag + ions from AgNPs reside in the matrix. Figure 11a shows the agar plate cultured with Gramnegative E. coli and then contacted directly with pure Figure 10.…”
Section: Antibacterial Activitymentioning
confidence: 99%